CHEMICAL COMPOSITION OF TWO SPECIES OF A. COMOSUS - Oluwaseyi Bukky Ovonramwen (Harčova Nauka ì Tehnologìâ)
Pineapple is a very common fruit that is grown by individuals in gardens or in commercial agriculture to cater for taste satisfaction and nutritional requirements of the populace. It is recognised as second rank tropical and subtropical fruits in the world with Nigeria producing 1.508 million tonnes in 2022. The physiochemical, proximate analysis, mineral and vitamin C components of two pineapple species (black and queen pineapple) bought from New Benin Market in Benin City, Edo State, Nigeria and their juices manually extracted were used to run these analyses. The study was carried out on proximate analysis: % moisture content, % ash content, % crude fat, % crude fiber and % crude protein as well as some selected minerals: Na, Mg, K, Fe, Zn and Ca, vitamin C and physiochemical properties of both of freshly prepared pineapple juice viz temperature, pH, total solid and sugar content using standard methods. The results obtained showed that black pineapple juice had the following composition; moisture content (85.30%), ash content (0.50%), total solids (14.60%), crude fiber (0.20%), crude fat (0.16%), crude carbohydrate (13.31%) and crude protein (0.57). While the juice extracted from queen pineapple contained: moisture content (87.50%), ash content (0.99%), total solids (12.50%), crude fiber (0.13%), crude fat (0.13%), crude carbohydrate (10.70%) and crude protein (0.54%). The temperature at which black and queen pineapple were analysed were 29.50 ℃ and 28.50 ℃ with pH 3.95 and 4.20, vit C and sugar (31.22 and 39.38 mg/100g), (12.70 and 14.32 obrix) respectively. The potassium (K), sodium (Na), calcium (Ca), magnesium (Mg), iron (Fe), zinc (Zn), and copper (Cu) were (62.66 and 52.45), (4.18 and 1.18), (2.30 and 2.90), (0.96 and 0.97), (0.10 and 0.23), (0.34 and 0.28), (0.00 and 0.00) in mg/L respectively. The minerals K, Zn, Fe and vitamin C contributed the highest percentage of nutrients needed to meet the daily requirement for proper functioning and development of a healthy body. It can be used in food fortification. There is absence of Cu, high calories from carbohydrate. Hence, it is recommended to be safe for drinking especially for constipation but excessive intake of these pineapple juices can lead to overweight, dental decay, stomach problems (like diarrhea), vomiting and nausea.